2022
DOI: 10.1186/s13065-022-00876-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel sensing probe using Terbium-sensitized luminescence and 8-hydroxyquinoline for determination of prucalopride succinate: green assessment with Complex-GAPI and analytical Eco-Scale

Abstract: A highly sensitive spectrofluorimetric method is developed for the determination of prucalopride succinate (PRU). The method depends on lanthanide-sensitized luminescence due to complex formation between the drug and terbium chloride (Tb+3) which is enhanced by the addition of 8 hydroxyquinoline (8HQ) and phosphate buffer (0.02 M, pH 3.2). The calibration curve was constructed over the linear range 10–300 ng/mL after excitation at 226 nm and measuring the emission of the ternary complex at 544 nm. The method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[14][15][16] The spectrophotometric methods suffered from limited sensitivity. While, the procedure of the rst spectrouorimetric method 14 was tedious, lengthy, utilized costly reagent (terbium chloride) and an environmental contaminating one (8-hydroxyquinoline). Although the second method 15 had simple procedure, its sensitivity was less than the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The spectrophotometric methods suffered from limited sensitivity. While, the procedure of the rst spectrouorimetric method 14 was tedious, lengthy, utilized costly reagent (terbium chloride) and an environmental contaminating one (8-hydroxyquinoline). Although the second method 15 had simple procedure, its sensitivity was less than the proposed method.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review revealed the determination of PRU using various analytical techniques including chromatographic [4][5][6][7][8][9][10], spectrophotometric [11] methods and only one reported spectrofluorometric procedure that uses luminescence reaction [12] but there is no quantification in the urine sample. Spectrofluorimetric technique is commonly used in drugs analysis either in dosage form or in biological fluids for its high sensitivity and simplicity [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For PCP analysis, literature reports document few spectrophotometric methods [3][4][5][6][7], spectrofluorimetric methods [8][9][10][11], chromatographic methods [12][13][14][15], and electrochemical methods [16,17]. The reported spectrophotometric methods had limited sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Four spectrofluorimetric methods were reported for PCP determination. However, the procedure of the first method involved the use of multiple reagents containing metal ions, buffers, and auxiliary chelating agents [8]. In addition, the reaction cocktail should be allowed to stand for at least 15 min before measuring the fluorescence of the formed product.…”
Section: Introductionmentioning
confidence: 99%